(untitled) (Anwer Khan Modern Medical College Journal, 2014)
Unlike many low and middle income countries, double burden diseases are serious problem in Bangladesh. Recently, proper understanding and the need for joint interventions against both infectious diseases and non-communicable diseases (NCD’s) has been gradually arising. Cardiovascular diseases (CVD’s), diabetes, cancers and chronic lung disease are the most frequent NCD’s whereas acute respiratory diseases, diarrhoea, neonatal sepsis and malaria are considered as infectious disease so far. Excess calories intake and unhygienic conditions are the most common risk factors, along with genetic predisposition and lifestyle choices. In addition, under nutrition in childhood also affects the human development in many aspects. The key controls of the situations are primary prevention through maintaining healthy life style during all phase of life. Action should focus controlling the risk factors in a unified fashion. Intervention at all levels of society, from communities to governments, private organizations and nongovernmental groups, is crucial for prevention by intensifying awareness of people about a perfect and healthy lifestyle. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18844 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 46-50